Accuracy of Point-Of-Care Knee Sonography for Diagnosis of Traumatic Anterior / Posterior Cruciate Ligament Tears Taking Magnetic Resonance Imaging as Gold Standard: A Systematic Review and Meta-Analysis: Accuracy of Point-Of-Care Knee Sonography - Raheem, Irum; Manzoor, Iqra; Rokhan, Bakht; Iqbal, Majid; Fatima, Zareen; Ali Khan, Amjad (Pakistan Journal of Health Sciences, 2023)
Knee joint is among the all the body's joints that are much prone to sustains injuries. Injury to the knee ligaments followed by instability can lead to serious deformity. The diagnosis of ligament injuries is frequently performed by using magnetic resonance imaging (MRI), but the use of ultrasonography remains controversial. This article reviews the current literature regarding the viability of point-of-care knee ultrasonography (POCUS) in comparison to knee magnetic resonance imaging (MRI) for the diagnosis of anterior cruciate ligament (ACL) and posterior cruciate ligament (PCL) injuries in those individuals who have experienced sudden knee trauma. The data span from 2000 to 2022 was used for the electronic database search (PubMed, Science Direct, Google Scholar). The systematic review included all studies that evaluated the diagnostic efficacy of ultrasound (U/S) compared to MRI as the gold standard and were completely available in English. The meta-analysis reviewing the efficacy of MSK-POCUS for anterior and posterior cruciate ligament injuries includes 30 papers. The overall ultrasonography sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were 76.02%, 92.77%, 92.25%, and 81.91% (95% CI), respectively. By assuring MRI as the gold standard in the diagnosis of ACL and PCL injuries, Point-of-care ultrasound (POCUS) reveals high accuracy. In individuals who have sustained acute knee injuries, the results of POCUS imaging might be serve to provide an initial diagnosis for additional pre-operative work-up.